Energy harvesting schemes for internet of things: a review - Doaa Abbas Fadil; Riyadh Jabbar Al-Bahadili; Mohammed Najm Abdullah (Institute of Advanced Engineering and Science, 2023)
As the internet of things (IoT) grows quickly, more people are interested in making wireless, low-power sensors. IoT systems currently use wireless sensors to collect reliable and accurate data in areas like smart buildings, environmental monitoring, and healthcare. Wireless sensors have typically been driven by batteries, which, although allowing for low total system costs, can have a significant impact on the whole network's lifetime and performance. The solution to this problem is energy harvesting (EH) from the environment. An EH is a technique for converting energy from an environmental source, such as heat, light, motion, or wind, into electric power. This paper describes many types of EH systems as well as some technological issues that must be solved before IoT energy harvesting solutions can be widely used.